Single-Session, Internet-Based Cognitive Behavioral Therapy to Improve Parenting Skills to Help Children Cope With Anxiety During the COVID-19 Pandemic: Feasibility Study - Korpilahti-Leino Tarja; Luntamo Terhi; Ristkari Terja; Hinkka-Yli-Salomäki Susanna; Pulkki-Råback Laura; Waris Otto; Matinolli Hanna-Maria; Sinokki Atte; Mori Yuko; Fukaya Mami; Yamada Yuko; Sourander Andre (JMIR Publications Inc., 2022)
Background
The COVID-19 pandemic has had a major impact on families’ daily routines and psychosocial well-being, and technology has played a key role in providing socially distanced health care services.
Objective
The first objective of this paper was to describe the content and delivery of a single-session, internet-based cognitive behavioral therapy (iCBT) intervention, which has been developed to help parents cope with children’s anxiety and manage daily situations with their children. The second objective was to report user adherence and satisfaction among the first participants who completed the intervention.
Methods
The Let’s Cope Together intervention has been developed by our research group. It combines evidence-based CBT elements, such as psychoeducation and skills to manage anxiety, with parent training programs that strengthen how parents interact with their child and handle daily situations. A pre-post design was used to examine user satisfaction and the skills the parents learned. Participants were recruited using advertisements, media activity, day care centers, and schools and asked about background characteristics, emotional symptoms, and parenting practices before they underwent the iCBT. After they completed the 7 themes, they were asked what new parenting skills they had learned from the iCBT and how satisfied they were with the program.
Results
Of the 602 participants who filled in the baseline survey, 196 (32.6%) completed the program’s 7 themes, and 189 (31.4%) completed the postintervention survey. Most (138/189, 73.0%) of the participants who completed the postintervention survey were satisfied with the program and had learned skills that eased both their anxiety (141/189, 74.6%) and their children’s anxiety (157/189, 83.1%). The majority (157/189, 83.1%) reported that they learned how to organize their daily routines better, and just over one-half (100/189, 53.0%) reported that the program improved how they planned each day with their children.
Conclusions
The single-session iCBT helped parents to face the psychological demands of the COVID-19 pandemic. Future studies should determine how the participation rate and adherence can be optimized in digital, universal interventions. This will help to determine what kinds of programs should be developed, including their content and delivery.